Evaluasi User Interface Desain Sistem Informasi Perpustakaan Pada Perguruan Husni Thamrin Medan - Chandra, Tintin (STMIK TIME, 2013)
Learn to represent natural essence by every human being. Process learn generally can be got from environment, work, school and family. Of education in school there have formal and also non is formal. At formal school, process learn to teach before always source of the book taught by teacher. To increase quality of education and instruction hence education so Perguruan Husni Thamrin Medan provide medium in the form of library to add student knowledge in learning and deepening science given by teacher. In management of library need the existence of a system assisting library head in its administration. Evaluation method is evalution predictive, where for predicate of problem of usage a product which this case library information system. With evaluation which isÂ to be obtained that information system the used have adequate and can overcome existing problem of management library Perguruan Husni Thamrin Medan.